Web crippling design of cold-formed steel built-up I-sections. (1st February 2022) - He, Jun; Young, Ben
Highlights: A total of 41 cold-formed steel built-up I-sections were tested under ETF, ITF, EOF and IOF loading conditions. Finite element models were developed to replicate the experiments. Parametric study of 258 specimens was performed. The existing codified web crippling design provisions were assessed. Design rules were proposed based on the unified equation and direct strength method. Abstract: This paper reports the experiments, numerical modelling and design of cold-formed steel built-up I-sections subjected to localised loadings. The built-up I-sections were made up of two equal-sized plain channels fastened back-to-back in the web. The web crippling tests were undertaken on 41 built-up I-section members under Interior-Two-Flange (ITF), End-Two-Flange (ETF), Interior-One-Flange (IOF) and End-One-Flange (EOF) loading conditions. The effects of the arrangement of screws along the web height were investigated. After the experiments, finite element (FE) analyses considering the initial local imperfections of the web of the specimens were performed and the validity of the FE models was assessed using the test results. A parametric investigation including 258 numerical simulations was conducted to expand the database and evaluate the influences of the screw arrangements in the web height. The test and numerical results indicated that the failure modes of the specimens with different screw arrangements were generally similar in each loading condition, and the screws located close to the flange-web junctions of the sections could generally provide maximum web crippling resistances of the built-up I-sections. The design recommendations on the arrangements of screws along the web height were proposed. The experimentally and numerically generated web crippling resistances were utilized to assess the current North American specification (AISI S100), Australian and New Zealand standard (AS/NZS 4600) and European code (EN1993-1-3). The results show that the existing codified design formulas lead to either conservative or highly unsafe results. Therefore, two sets of design formulas were derived on the basis of unified equation and direct strength method.